Crisis económica y determinantes de la oferta de trabajo femenino en México : 1994-1995 - Zenteno, René M. (El Colegio de México A.C., 1999)
Women's swift incorporation into the labor market constitutes one of the most important research topics in light of the rapid social, economic and demographic changes undergone by Mexico over the past two decades. Among many other factors, various studies have argued the existence of a close link between this process of social change in women, and the economic crisis faced by many Mexican families during the long period of productive re-structuring. The basis of this argument is largely derived from the quantification of a phenomenon that was unusual in Mexico before the 1980s: the growing economic participation of women of an advanced age, those with low schooling attainment, women who are either married or living with their partner, and finally, of women with small children. In other words, of social groups that had traditionally shown very little propensity towards working outside the home. This article constitutes a conjunctural study whose central aim was to conduct an empirical assessment of the relationship between economic crisis and this new profile of female labor. To do this, the determinants of the supply of female urban labor during the first few months of the most recent economic crisis were studied and compared with the prevailing situation exactly one year earlier. Data from the National Urban Employment Survey show that the real income of workers, open unemployment and the employment rates of men in salaried jobs were the urban employment conditions most severely affected by the recession. The multivariate analyses conducted yielded three significant results. First, that the impact of the crisis on the economic participation of men and women varied significantly between the country's major urban centers. Second, that with the exception of women with the lowest schooling attainment, it is possible to establish the existence of a close link between higher employment among older women in a union who live in households where there are children under the age of seven, and a situation of economic crisis. Third, that several of these changes did not only take place in labor markets where female economic participation rose during the period, but also in those where it remained stable or fell.